Cyprus before 1974 - Varnava, Marilena. (London)
viii, 275 sayfa
Keywords: “Focusing on the period from September 1964, when Senor Galo Lasso Plaza assumed the UN mediatory role, to the coup d'etat and the Turkish invasion ten years later, Cyprus Before 1974 seeks to unpick the internal conflicts which led to the failure of the peace process in Cyprus. Marilena Varnava studies three phases: Plaza's mediation of 1964-1965; the negotiating impasse on the island during the period 1965-1967; and finally the inter-communal talks of 1968-1974. Varnava argues persuasively that each of these successive phases, particularly the latter two, were inextricably tied to political and social developments within the two main communities on the island itself. In particular, Cyprus before 1974 focuses on the events of 1968 - when the Greek-Cypriot political leadership, and the President of the Republic of Cyprus Archbishop Makarios III, failed to grasp the nature of the changes within the island's post-independence arena. Recurrent attempts within both communities during the talks of that year to create faits accomplis favourable to their own bargaining positions served to heighten the barriers to a stable and peaceful outcome. This study enlarges our understanding of the underlying issues which the Turkish invasion of 1974 were to throw into stark relief and is essential reading for all those who study the Cyprus problem and conflict resolution“ -- Yayıncı.